AB0268 Metatarsophalangeal Joint Dislocation has Clinical Impact on Global Functional Impairment in Patients with Rheumatoid Arthritis – a Cross-Sectional Study from Kurama Cohort-. (9th June 2015) - Ito, H.; Hamamoto, Y.; Furu, M.; Hashimoto, M.; Fujii, T.; Ishikawa, M.; Azukizawa, M.; Terao, C.; Mimori, T.; Matsuda, S.
Abstract : Background: Forefoot deformity is one of the most dominant deformities in patients with rheumatoid arthritis (RA). However, which deformity has the most clinical relevance on global functional impairment in the lower extremities remains to be investigated. We conducted a cross-sectional study on this subject using a comprehensive RA cohort (KURAMA cohort). Objectives: To investigate relationship among forefoot deformities and the influence of functional impairment in the lower extremities from a RA cohort. Methods: A cross-sectional clinical cohort survey was performed on 740 feet of 370 patients with RA in KURAMA cohort. The average age was 62.8 years old, and the female ratio was 87.6%. Radiographic measurements such as hallux valgus angle (HV angle), metatarsal deformities (M1M2 and M1M5 angles), Larsen grade of the metatarsophalangeal joints (MTP joints), and lateral angle and dislocation of MTP joints were obtained along with clinical data such as age, duration of the disease, seropositivity, disease activity and medication. Results: HV, M1M2, M1M5 angles and lateral angle of MTP joint were significantly correlated each other (p<0.05). The numbers of dislocation of MTP joint were most significantly correlated with HV angle and lateral angle of MTP joint (ρ=0.839, 0.514, respectively), while much less with M1M2 and M1M5 angles (ρ=0.277, 0.135, respectively). On the other hand, HV angle and lateral angle of the MTP joint had significant correlation with duration of disease, Steinbrocker stage, DAS28-ESR, CRP, and HAQ, while M1M2 and M1M5 angles did only with duration of the disease. When functional impairment of the lower extremity (lower HAQ) was exclusively counted among the scores of HAQ, multivariate analyses showed the number of dislocation of MTP joint was a sole independent significant predictor for lower-HAQ. Conclusions: MTP joint dislocation has the most significant influence on functional impairment in the lower extremities among forefoot deformities in patients with RA. To avoid daily disability, MTP joints should be paid careful attention and be treated appropriately. Disclosure of Interest: H. Ito Grant/research support from: Takeda, Mitsubishi Tanabe, Chugai, Pfizer, Astellas Pharma, Daiichi Sankyo, Y. Hamamoto: None declared, M. Furu Grant/research support from: Mitsubishi Tanabe, Chugai, Eisai, Bristol-Myers, M. Hashimoto Grant/research support from: Mitsubishi Tanabe, Chugai, Eisai, Bristol-Myers, Astellas Pharma, T. Fujii Grant/research support from: Mitsubishi Tanabe, Chugai, Eisai, Bristol-Myers, M. Ishikawa: None declared, M. Azukizawa: None declared, C. Terao: None declared, T. Mimori: None declared, S. Matsuda: None declared